Green Entrepreneurship and Performance Entrepreneurship Seen From the Aspect of Culture and Motivation: Preliminary Study - Rinda Fithriyana; Rahmi Fahmy (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The article discusses in more depth as a preliminary study on the development of green entrepreneurship, entrepreneurship performance seen from the aspect of culture and motivation. Articles are compiled using the literature study method. Literature study is done by looking at the results of the research and the instruments that can be used for preliminary studies. Green entrepreneurship is now getting better, with increasing concern for the environment from various circles of society, especially for companies, especially MSMEs. Another aspect that triggers the development of green entrepreneurship is culture and motivation. With these two aspects, it is expected to be able to improve entrepreneurial performance.